The Moderating Effect of Accounting Conservatism on Managerial Ownership and Growth Opportunity Relationship - Akbar, Muhammad; Romadhon, Fitri; Fitri, Alfiana; Pratama, Ahmad Rizal Restu (InFestasi, 2024)
The application of the accounting conservatism method in the company's financial statements is essential for company managers in their consideration of strategy development. In uncertain global economic conditions, the application of the precautionary principle or accounting conservatism in financial statements is needed to maintain the stability of the company's financial condition. This study aims to test and analyze the effect of managerial ownership and growth opportunities on accounting conservatism with leverage as a moderating variable. This study uses secondary data in the form of annual financial reports on property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) and Indonesian Capital Market Directory. This study used a purposive sampling technique. The results showed that managerial ownership affects accounting conservatism, while growth opportunity does not affect accounting conservatism. For leverage used as a moderating variable, it is unable to moderate the effect of managerial ownership and growth opportunity on accounting conservatism. This study can help investors and regulators understand the role of managerial incentives in shaping financial reporting behavior. Companies and regulators may want to consider ownership structure when evaluating financial transparency and risk.